Comparative genotoxic and histopathological effects of copper nanoparticles and copper chloride in goldfish (Carassius auratus) - GÜLSOY, NAGİHAN (My University, 2024)
The purpose of the current study was to ascertain the comparative effects of compounds, copper (II) oxide nanoparticles (nCuO) and copper salt (CuCl2), on the genotoxicity and histopathology of goldfish (Carassius auratus) for acute exposures of 24, 48, 72, and 96 h (concentrations: 100, 150, 200, and 1, 1.5, 2 mg/L nCuO and CuCl2, respectively). The peripheral erythrocytes were obtained for that purpose from the caudal vein in each individual. The Comet assay and micronucleus test were used to evaluate genotoxicity, and gill tissues were prepared for histopathology. High levels of nCuO and CuCl2 concentrations and acute exposure (96-hour) increased the percentage of DNA in the comet tails, olive tail moments, and micronucleus counts showed genotoxic effects on exposed fish. Also, the gill tissue alterations were observed and changed as the lifting of the respiratory epithelium, hyperplasia of the lamellar epithelium, incomplete, and complete fusion of several lamellae, and hypertrophy. Genotoxicity for nCuO and CuCl2 was discovered to be a concentration and time-dependent phenomenon. In general, experimental groups showed significant impacts (p=0.05) on concentrations and exposure periods, which may contribute to understanding the mechanism of nCuO and CuCl2-induced genotoxicity in the fish.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Çevre / Ekoloji; ÇEVRE BİLİMLERİ; Agriculture & Environment Sciences (AGE); ENVIRONMENT/ECOLOGY; ENVIRONMENTAL SCIENCES; Su Bilimi; Yaşam Bilimleri; Aquatic Science; Life Sciences; Comet assay; Copper; Genotoxicity; Gill histopathology; Micronucleus; Toxicity